Effective choice of ZnO formation methodology for highly stable polymer solar cells under damp-heat (85 °C/85% RH) and light soaking conditions. Issue 3 (6th December 2022) - Lee, Seung-Hoon; Park, Byoungwook; Eom, Seung Hun; Ko, Seo-Jin; Lee, Changjin; Yoon, Sung Cheol
Abstract : The damp-heat stability and photostability of solar cells were investigated depending on the ZnO fabrication methodology. Although the initial PCEs of the devices were similar, the ZnOs affected the solar cell performance after the aging process. Abstract : The damp-heat stability at 85 °C/85% relative humidity (85/85) and photostability for 1000 h of polymer solar cells (PSCs) with various ZnO electron extraction layers (EELs) fabricated using different precursors and methodologies were comprehensively investigated. ZnO nanoparticles (ZnO NPs), ZnO fabricated by the sol–gel reaction, and ZnO formed from a pyrophoric precursor were used in this study. Although the initial performances of the PSCs depending on the type of ZnO EELs are similar, the damp-heat stability and photostability of the PSCs are completely different. 85/85 and light soaking stress generate localized states in the ZnO EELs and their interfaces, resulting in an increase in the recombination loss and a decrease in the collection efficiency and mobility of the PSCs. The most stable PSCs with a PTB7-th:EH-IDTBR-based photoactive layer were achieved using ZnO NPs, exhibiting the lowest initial disorder and highest initial pure ZnO/oxygen defect proportion among the ZnO EELs. The corresponding devices retained 85% and 81% of their initial power conversion efficiencies (PCEs) after damp-heat and photostability tests for 1000 h, respectively. Finally, the stability of state-of-the-art PM6:Y6-based PSCs (PCE ∼ 14%) using ZnO EELs was also evaluated to prove their reproducibility with other active materials.